On the nose: nasal neurostimulation as a technology countermeasure for sinonasal congestion in astronauts - Ax, Timon; Zimmermann, Philipp H.; Bothe, Tomas L.; Barchetti, Karen; de Paiva, Cintia S.; March de Ribot, Francesc; Jensen, Slade O.; Millar, Thomas J. (Frontiers in Physiology, 2025)
Human spaceflight subjects the body to numerous and unique challenges. Astronauts frequently report a sense of sinonasal congestion upon entering microgravity for which the exact pathomechanisms are unknown. However, cephalad fluid shift seems to be its primary cause, with CO2 levels and environmental irritants playing ancillary roles. Current management focuses on pharmacotherapy comprising oral and nasal decongestants and antihistamines. These are among the most commonly used treatments in astronauts. With longer and more distant space missions on the horizon, there is a need for efficacious and payload-sparing non-pharmacological interventions. Neurostimulation is a promising countermeasure technology for many ailments on Earth. In this paper, we explore the risk factors and current treatment modalities for sinonasal congestion in astronauts, highlight the limitations of existing approaches, and argue for why neurostimulation should be considered.